Theoretical study on the structural, electronic, and optical properties of BnCn (n = 1–13) clusters - Xiaojie Chen; Chen Zhang; Bin Song; Pimo He (Materials Research Express, 2020)
We applied density functional theory (DFT) calculations to investigate the low-energy geometries and electronic characteristics of stoichiometric B _n C _n ( n  = 1–13) clusters. We performed harmonic vibration frequency analysis to ensure that the ground-state isomers are the real local minima. B _n C _n clusters tend to evolve from planar and annular structures to quasiplanar bowl structures to maintain the lowest structural energy as cluster size n increases. The clusters with even n have large HOMO–LUMO gaps and high stability. We used the time-dependent DFT (TDDFT) calculations to acquire the optical absorption spectra for the lowest-energy B _n C _n ( n  = 4, 6, 8, 10, 12) clusters. The clusters exhibit strong absorption in the ultraviolet region. With the increasement of n, the absorption of clusters, particularly that of the B _8 C _8 cluster, intensifies in the visible region. Therefore, the clusters investigated in this work can be used to fabricate novel two-dimensional materials for visible-light absorption and have potential applications in various fields, such as catalysis.